Propagative plasmons in graphene investigated by simulation method and infrared spectroscopy - Legrand, David (2019)
Graphene physics and plasmonics are two fields which, once combined, promise a variety of exciting applications. One of those applications is the integration of active nano-optoelectronic devices in electronic systems, using the fact that plasmons in graphene are tunable, highly confined and weakly damped. Before achieving these active device, a crucial challenge remains : finding a platform enabling a high propagation of Graphene Plasmons Polaritons (GPPs). In this framework, a full study of the propagation of plasmons through suspended graphene is addressed. This study start by reviewing the theoretical and experimental research achievement related to the really recent emerging field of graphene plasmonics. A numerical investigation by FDTD method is presented, and the conditions for a realisation of the study of graphene plasmons in suspended graphene are analysed. A design of the sample with an experimental process is proposed. Finally, an experimental study from the fabrication in clean room, then the characterisation of graphene and plasmonics structure, to the optical measurement through Scanning Near-field Optical Microscopie is presented.